2018
DOI: 10.5751/es-10175-230321
|View full text |Cite
|
Sign up to set email alerts
|

The implications of group norms for adaptation in collectively managed agricultural systems: evidence from Sri Lankan paddy farmers

Abstract: A growing literature seeks to explore the factors shaping adaptation to climate change. In collectively managed common pool resource systems, there is often a tension between behavior that benefits the individual and actions that benefit a larger group. Resource users in sustainable systems must therefore work together to ensure outcomes that are beneficial to the group as a whole. However, in the face of changing social, political, and environmental conditions, community norms may change, leading to the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Indeed, empirical research supports this suggestion, demonstrating that achieving cooperative consensus and internalizing corresponding cooperative norms are essential for making decisions that maximize collective (rather than individual) benefit (Kerr et al, 1997;. The relevance of group norms for motivating sustainable resource use has also been demonstrated in field contexts related to over-consumption of environmental resources (Goldstein, Cialdini, & Griskevicius, 2008;Schultz et al, 2007), including agricultural practice (Fielding et al, 2008), and its adaptation to climate change in non-Western contexts (Tozier de la Poterie, Burchfield, & Carrico, 2018;Truelove et al, 2015).…”
Section: Group Processes and Communal Land Management 12mentioning
confidence: 91%
“…Indeed, empirical research supports this suggestion, demonstrating that achieving cooperative consensus and internalizing corresponding cooperative norms are essential for making decisions that maximize collective (rather than individual) benefit (Kerr et al, 1997;. The relevance of group norms for motivating sustainable resource use has also been demonstrated in field contexts related to over-consumption of environmental resources (Goldstein, Cialdini, & Griskevicius, 2008;Schultz et al, 2007), including agricultural practice (Fielding et al, 2008), and its adaptation to climate change in non-Western contexts (Tozier de la Poterie, Burchfield, & Carrico, 2018;Truelove et al, 2015).…”
Section: Group Processes and Communal Land Management 12mentioning
confidence: 91%
“…Previous research suggests that cooperative norms stem from strengthening group cohesion [40], and a number of studies demonstrate that developing and internalising cooperative social norms is essential for successfully managing shared resources [31,[41][42][43]. There is also evidence supporting the role of social norms in cooperation around shared environmental resources, including agricultural land [44][45][46][47]. Overall, it could be suggested that CNRM group identification would be related to stronger cooperation around resources shared by that group, and this link could be mediated by stronger sense of collective efficacy, higher trust, and cooperative norms.…”
Section: Group Identification and Cooperative Behaviourmentioning
confidence: 99%